(untitled) (Third Sector Social Economic Review, 2022)
Environmental wastes increasing with the industrialization process have caused environmental problems to come into prominence worldwide. Therefore, the relationship between economic growth and environmental pollution has become the center of attention for many researchers, and many studies have been conducted. One of the most important hypotheses that reveal the relationship between these variables is the Environmental Kuznets Curve (EKC). In this context, the study aimed to examine the validity of the EKC, which revealed an inverse-U-shaped relationship between economic growth and environmental pollution, for Turkey in the period between 1990 and 2015. The relationship between environmental pollution and economic growth in the study was analyzed through the ARDL limit test. According to the analysis results, it was concluded that the EKC hypothesis was valid for Turkey in the period mentioned. In this respect, environmental degradation initially rises as economic growth increases, but environmental pollution decreases with the increase in environmental consciousness after a certain threshold growth level. Moreover, the study elucidated that the increase in the amount of renewable energy consumption reduced environmental pollution. Accordingly, it is recommended to produce with clean technology that will enhance the environmental quality in the production process and implement a stable growth policy that will increase the amount of renewable energy consumption within the total energy consumption. Furthermore, legal regulations can be made to promote the use of environmentally friendly technologies in production, and tax reductions or various investment supports can be provided within this framework. Key Words: Environmental Kuznets Curve, Economic Growth, Environmental